Animations in LaTeX for teaching Simple Harmonic Motion: Animaciones en LaTeX para la enseñanza del Movimiento Armónico Simple - Jiménez Carballo, Carlos (2025)
This work aims to comprehensively illustrate the use of LaTeX for the creation of educational animations pertaining to the fundamental concepts of physics, with a specific focus on the study of Simple Harmonic Motion (SHM). In this context, we present the TikZ and animate packages, which the LaTeX environment uses to create animations from vector graphics. Subsequently, the basic codes necessary to implement five animations of a particle attached to a spring that describe simple harmonic motion are shown in detail. The animations aim to facilitate a smooth and understandable transition between the complex mathematical equations that describe a physical phenomenon and their visual representation, thereby allowing for better comprehension.